Novel 1-((benzoimidazole-2-yl)methyl)-3-phenyl- 1,4-dihydropyrazole-5-one and their derivatives: Synthesis and preliminary cytotoxicity test as anti-breast cancer - Abubaker M.; Ngah C.W.Z.C.W.; Ahmad M.; Kuswandi B. (American Scientific Publishers, 2024)
Indexed by SCOPUS/ERA